Metabostemness: A New Cancer Hallmark - Menendez, Javier A.; Alarcón, Tomás (Frontiers in Oncology, 2014)
The acquisition of and departure from stemness in cancer tissues might not only be hardwired by genetic controllers, but also by the pivotal regulatory role of the cellular metabotype, which may act as a “starter dough” for cancer stemness traits. We have coined the term metabostemness to refer to the metabolic parameters causally controlling or functionally substituting the epitranscriptional orchestration of the genetic reprogramming that redirects normal and tumor cells toward less-differentiated CSC cellular states. Certain metabotypic alterations might operate as pivotal molecular events rendering a cell of origin susceptible to epigenetic rewiring required for the acquisition of aberrant stemness and, concurrently, of refractoriness to differentiation. The metabostemness attribute can remove, diminish, or modify the nature of molecular barriers present in Waddington’s epigenetic landscapes, thus allowing differentiated cells to more easily (re)-enter into CSC cellular macrostates. Activation of the metabostemness trait can poise cells with chromatin states competent for rapid dedifferentiation while concomitantly setting the idoneous metabolic stage for later reprogramming stimuli to finish the journey from non-cancerous into tumor-initiating cells. Because only a few permitted metabotypes will be compatible with the operational properties owned by CSC cellular states, the metabostemness property provides a new framework through which to pharmacologically resolve the apparently impossible problem of discovering drugs aimed to target the molecular biology of the cancer stemness itself. We are embarking on one of the cancer field’s biggest challenges, namely the discovery of the key metabolic features and the elite metabolites that influence chromatin structure and epigenetic circuits in charge of CSC reprogramming and the incorporation of novel metaboloepigenetic strategies that can effectively hamper cancer initiation and progression at the stem cell level.